Determination of the molar mass of the humic substances of the Chubut River (Argentina) by electrospray ionization mass spectrometry - Scapini, Maria del Carmen (2013)
Here, we studied the number-average molar mass of the humic substances of the Chubut River (Argentina) in order to progress in their characterization. We used electrospray ionization mass spectrometry in positive mode because of its high accuracy and non-destructive nature. The result obtained (818. Da) is a relatively low value, typical of fulvic acids.